Assessing Dental Educators' Preparedness for E-Learning: A Cross-Sectional Multi-Country Analysis (Medical Forum Monthly, 2024)
Objective: This study assessed dental educators' self-perceived readiness for e-learning in multiple institutions in six different countries.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the College of Dentistry, King Faisal University Al- Ahsa, Saudi Arabia, from April to September 2023.Methods: Participants were invited via email to complete an online survey, which was based on the Teacher Readiness for Online Learning Measure (TRLOM) scale, to assess their readiness for online learning. Participants were recruited using convenience and snowball sampling methods. The study included educators from Egypt, India, Nigeria, Pakistan, Saudi Arabia, and Sudan.Results: This study included 96 dental educators; 53.1% were males, and 81.3% were in public institutes. The institutes provided just (8.3%) of the internet access devices for the educators. A majority (57.3%) of the educators showed high communication self-efficacy, (53.1%) showed high-perceived institutional support, (49%) rated themselves as self-directed learners, and (62.5%) stated high learning transfer self-efficacy. The learning transfer self-efficacy construct significantly correlated with all other constructs, which indicates that these are essential factors for the success of the e-learning process. It was also clear that the educator's self-directed learning significantly correlated with institutional support and communication self-efficacy.Conclusion: Dental educators in investigated institutes showed confidence in their self-perceived readiness for e-learning. However, institutional support is crucial to overcome resource limitations and enhance e-learning effectiveness. Institutions must take proactive steps to prepare and motivate educators to transition to e-learning